Квадрофілярна антена для засобів РЕБ - Колесніков, П. (ХНУРЕ, 2025)
The work aims to describe and design one of the possible types of quadrafilar antennae. The antenna has a wide range of operating frequencies and a "dome" directional pattern, which allows it to be used in modern tactical-level electronic warfare.
Keywords: квадрофілярна антена; засоби РЕБ